Combing mechanical side-deep fertilization and controlled-release nitrogen fertilizer to increase nitrogen use efficiency by reducing ammonia volatilization in a double rice cropping system - Chen, Zhaoming; Wang, Qiang; Ma, Jinchuan; Zhao, Jun; Huai, Yan; Ma, Junwei; Ye, Jing; Yu, Qiaogang; Zou, Ping; Sun, Wanchun; Zhang, Gengmiao; Zhao, Yujie (Frontiers in Environmental Science, 2022)
Ammonia (NH3) volatilization losses result in low nitrogen use efficiency (NUE) and various environmental impacts in agroecosystems. Machine-transplanted rice with side-deep fertilization (MRSF) has been recommended as an effective alternative to traditional transplantation with manual broadcasting of fertilizer. Controlled-release nitrogen fertilizer (CRF) can enhance rice yield and NUE in paddy fields. However, there is scarce information about combined effects of MRSF and CRF on ammonia (NH3) volatilization loss and rice grain yield, N recovery efficiency (NRE)NUE, net economic benefit (NEB) in a double rice cropping system. In this study, a field experiment was conducted to evaluate the impact of MRSF with CRF on grain yields, NUE and economic returns of early rice and late rice from 2019–2021, as well as NH3 emissions in two rice seasons (2019 and 2021). Six treatments were designed as no N fertilizer (N0), compound fertilizer broadcasting (CFB), compound fertilizer side-deep placement (CFD), CRF broadcasting (CRFB), CRF side-deep placement (CRFD1), and single side-deep placement of CRF (CRFD2). The results showed that the CFD and CRFB treatments decreased NH3 volatilization while enhancing or maintaining rice yield and NUE NRE compared to the CFB treatment. MRSF with CRF (CRFD1 and CRFD2) significantly reduced NH3 emissions of early and late rice by 57.6–67.9% and 62.2–80.9% by decreasing the NH4+–N concentrations in the surface water compared to the CFB treatment, respectively. Rice grain yields in the MRSF with CRF treatments increased by 3.9–17.3% in early rice and 5.4–21.6% in late rice relative to the CFB treatment. In addition, MRSF with CRF treatments improved NUE NRE for early and late rice from 32.1–36.2% and 21.3–28.4% in the CFB treatment to 48.4–61.2% and 39.7–62.3%, respectively. The yield-scale NH3 volatilization losses were reduced under the MRSF with CRF treatments by 61.2–71.5% in early rice and 67.4–84.3% in late rice. Furthermore, MRSF with single basal application of CRF reduced time-consuming and labor-intensive while increasing rice yields and net economic benefits. Overall, co-application of MRSF and CRF can reduce NH3 emissions, and improve rice yield, NUE NRE and profitability in double rice cropping systems.